Design and validation of a power modulation system for residential demand-side management - Aaron Goldin; Elizabeth Buechler; Ram Rajagopal; Juan M. Rivas-Davila (International Journal of Electrical Power & Energy Systems)
Residential loads have great potential to provide flexibility and other services to the grid, but many legacy or non-networked loads need additional hardware to enable such functionality. Currently available devices (e.g., smart thermostats or load control switches) that equip legacy loads with energy management features, provide narrow functionality to address specific use cases.We propose the Smart Dim Fuse (SDF), a unified system with general purpose hardware, to enable legacy residential loads with versatile grid-interactive functionalities. By combining sensing, power electronics, and load modeling into a single architecture, the SDF offers comprehensive capabilities that would otherwise require a large number of disparate devices that are not inherently compatible. Based on a thoroughly tested prototype, we suggest that such a device can deliver this flexibility at a levelized cost of 0.018-0.052 $/kWh. The prototype power electronics operates at efficiencies between 96.4-98.5% at full load. The system can deliver fast load power modulation with a mean average percentage error below 1.8%.